Primary amoebic meningoencephalitis due to Naegleria fowleri - Angrup, A; Chandel, L; Sood, A; Thakur, K; Jaryal, SC (Journal of Institute of Medicine Nepal, 2011)
The genus Naegleria comprises of free living ameboflagellates found in soil and fresh water. More than 30 species have been isolated but only N. fowleri has been associated with human disease. N. fowleri causes primary amoebic meningoencephalitis (PAM), an acute, often fulminant infection of CNS. Here we report a rare and first case of PAM in an immunocompetent elderly patient from this part of the country. Amoeboid and flagellate forms of N. fowleri were detected in the direct microscopic examination of CSF and confirmed by flagellation test in distilled water, demonstrating plaques /clear areas on 1.5% non nutrient agar and its survival at 42°C. Keywords: Meningitis; Naegleria fowleri; primary amoebic meningoencephalitis DOI: http://dx.doi.org/10.3126/joim.v32i2.4949 Journal of Institute of Medicine, August, 2010; 32: 56-59